2021
DOI: 10.1109/ojcas.2020.3041239
|View full text |Cite
|
Sign up to set email alerts
|

Performance Comparison of Baseband Signaling and Discrete Multi-Tone for Wireline Communication

Abstract: Limits of data rate over a wireline channel depend on the channel characteristics, the signaling or modulation scheme, and the complexity one can afford for its implementation. This article compares two signaling schemes, namely baseband and discrete multi-tone (DMT), for two example channels, one with a smooth frequency response and one with a notch frequency response, to examine how far each can push the data rate towards the maximum achievable data rate, derived from Shannon Capacity formula. INDEX TERMS Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Moreover, unlike 4-PAM systems, each equalizer tap in a DMT system is optimized independently. This simplifies the control algorithm leading to more optimal spectral utilization with the potential to achieve a higher capacity [2], [8], [9], [19]. However, in DMT, three sources of impairment remain: Inter-Frame-Interference (IFI), attenuation, and phase delay.…”
Section: B Equalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, unlike 4-PAM systems, each equalizer tap in a DMT system is optimized independently. This simplifies the control algorithm leading to more optimal spectral utilization with the potential to achieve a higher capacity [2], [8], [9], [19]. However, in DMT, three sources of impairment remain: Inter-Frame-Interference (IFI), attenuation, and phase delay.…”
Section: B Equalizationmentioning
confidence: 99%
“…As mentioned in Section II, DMT systems employ channel optimization algorithms to determine the constellation size for each bin [2], [8]. Constellations begin small and grow incrementally until the channel capacity is reached [15].…”
Section: A Adaptive Equalizer Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…W IRELINE data rates are marching beyond 200Gb/s [1], but a question remains as to how much room is left in this march and how to close the remaining gap to Shannon's capacity limit [2]. In the pursuit to close this gap, alternative signal modulation techniques are being considered, including multi-carrier schemes [3][4] [5][6] [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Prior-arts such as [19], [20] showed that 56-112 Gb/s optical data communication is feasible with discrete multi-tone (DMT) modulation (i.e., baseband OFDM with variable bit-loading for each OFDM sub-channel), and [21] demonstrated a 56 Gb/s RX data-path silicon for electrical links. System-level modeling of a DMT serial link for > 100 Gb/s applications is provided in [22], and [23] compared DMT link and PAM-2/4/8 for ultra-high-speed links both with smooth channels and multi-drop-bus (MDB) interfaces. Timing recovery system with adaptive equalization for wireline DMT links is proposed in [24].…”
Section: Introductionmentioning
confidence: 99%